Obtenção da L-asparaginase de Aspergillus niger suplementados com a semente de Euterpe oleracea Mart e análise de sua atividade antitumoral in vitro - DUARTE, Suzane Meriely da Silva (2024)
Cervical cancer caused by the human papillomavirus (HPV) is diagnosed in women all over the planet, mainly in developing countries, and problems such as scarcity or even lack of health services and informative and preventive education end up contributing for the advancement of this type of cancer. Several researches are constantly carried out to create pharmaceutical products that reduce the proliferation of cancer cells, and in this study the enzyme L-asparaginase was seen as promising, given its anticarcinogenic capacity against different oncongenic alterations, among them, lymphoproliferative, as is the case with acute lymphoblastic leukemia (ALL). The fungus Aspergillus niger was chosen for this study because it is a source with potential capacity for L-asparaginase production, being widely distributed in nature. The objective of this work was to obtain L-asparaginase produced by A. niger supplemented with Euterpe oleracea Mart seed flour, analyzing the in vitro antitumor activity of the enzyme in RAW, GM, HeLa and SiHa cell lines. E. oleracea Mart seed flour was obtained and subsequent analysis of phenolic compounds, flavonoids and in vitro biological activity of the seed flour substrate; bioprospecting of the enzyme in different types of fungi; verification of L-asparaginase production in semi-solid and submerged fermentation; molecular identification of A. niger using the Polymerase Chain Reaction (PCR); purification of L-asparaginase; biochemical characterization (optimum pH and temperature, enzyme kinetics, influence of ions and surfactants and stability in organic solvents); analysis of enzymatic cytotoxicity in RAW, GM, HeLa and SiHa cell lines; morphological viability in HeLa cells and cell migration assay in HeLa and SiHa cells. The results found showed that A. niger presents greater enzymatic activity and protein concentration in semisolid fermentation, using E. oleracea Mart seed flour as a source of nutrients. The enzyme presented an optimum pH of 9.0 and an optimum temperature of 50°C, resistance to various ions and surfactants and a reduction in the proliferative activity of HeLa cells, showing that L-asparaginase from A. niger may be a future alternative for treatment. of cervical cancer caused by HPV 18.